The depression distress amplification model in adolescents: A longitudinal examination of anxiety sensitivity cognitive concerns, depression and suicidal ideation. (June 2015) - Capron, Daniel W.; Allan, Nicholas P.; Ialongo, Nicholas S.; Leen-Feldner, Ellen; Schmidt, Norman B.
Abstract: Adolescents with comorbid anxiety and depression are at significantly increased risk of suicide. The recently proposed depression distress amplification model appears to have promise for explaining the relations between anxiety, depression, and suicidality, but it has not been tested in adolescents. Participants were 524 adolescents followed over two years. Baseline data for the current report were collected by trained interviewers while the adolescents were in eighth grade. Data were obtained in the same manner when the adolescents were in tenth grade. Baseline anxiety sensitivity cognitive concerns significantly predicted suicidal ideation two years later, above and beyond baseline suicidal ideation and depression. Further, consistent with the depression distress amplification model, anxiety sensitivity cognitive concerns interacted with depressive symptoms to predict suicidal ideation. This report extends the empirical and theoretical support for a relationship between anxiety sensitivity cognitive concerns and suicidality.